Komunikasi Ritual dalam Surtanah - Khiyaroh, Intihaul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Ritual communication in the Surtanah tradition, a socio-religious practice performed by communities on the first day after death. This tradition is understood as a manifestation of the acculturation of local culture with Islamic teachings that emphasize prayer, almsgiving, and social solidarity. The purpose of this study is to analyze the role of ritual communication in Surtanah as a means of transmitting values, strengthening religious identity, and contributing to building global harmony through the values of compassion, tolerance, and togetherness. The research method used is qualitative with an ethnographic communication approach through participant observation and in-depth interviews with religious leaders, traditional practitioners, and the community. The results show that ritual communication in Surtanah functions not only as a means of prayer for the deceased but also as a medium for social integration, a symbol of cultural acculturation, and the strengthening of religious moderation. In conclusion, Surtanah reflects a harmonious dialogue between culture and Islam that is relevant to strengthening universal humanitarian values.